Due Diligence and Disclosure – A Quagmire in Corporate Acquisition Contract: Case Reflection on Elon Musk-Twitter - Ngwakwe, Collins (Acta Universitatis Danubius. Juridica, 2022)
Disclosure requirements in business contracts of mergers and acquisition remain somewhat nebulous with attendant post-contract quagmire and disputes between buyers and sellers. This paper aims to initiate a conceptual discussion on disclosure and diligence in acquisition contract with a slant on the Musk-Twitter acquisition and to propose a framework for achieving conflict-free acquisition. The paper draws insight from extant theorisation of disclosures in mergers, acquisitions, and risk sharing. Approach: The paper is conceptual and applies a critical discussion of current professional and scholarly literature toward a conceptual framework. Findings: based on the review of professional and scholarly papers, the paper finds apparent ambiguity regarding disclosure requirements during contract of acquisition. It also finds new clarity bourgeoning with newly decided business acquisition cases and new research regarding contestations that emerge after signing acquisition contracts. Furthermore, there is a paucity of a scholarly framework to proffer a guide to the seller and buyer toward reducing grey issues and attendant conflicts. Implications: the findings offer professional and academic implications regarding the need for caution, information, and advice in acquisition contracts. The paper is also significant for business schools as it provides a current teaching case on the dilemma in mergers and acquisition contracts. Furthermore, this paper initiates a new research agenda for further researchers to extend the discussion on acquisition contracts by top investors. Value: Using the most current case, the paper contributes to the field of merger and acquisition contracts by proposing a framework to reduce conflict and risks in corporate acquisition.